"Hot-node" controlled facile synthesis of 3D rare earth micro-networks with symmetry deviation induced high luminescence. Issue 34 (10th August 2020) - Chen, Bin-Bin; Lv, Jian; Chang, Shuai; Wang, Xiao-Yuan; Qian, Ruo-Can; Li, Da-Wei
Abstract : This work develops a facile and gram-scale synthetic strategy controlled by "hot-nodes" for the preparation of high luminescence 3D assembled RE-MNs with a symmetry deviation induced transition effect. Abstract : Controlled self-assembly is a powerful strategy for building mesoscopic superstructures. However, the construction of high luminescence, millimeter-sized and spatially well-defined 3D rare earth (RE) material assemblies is a challenging objective. Apart from ligand sensitized luminescence of RE 3+ ions, improving their luminescence efficiency by changing the symmetry of the coordination environment of RE 3+ ions is a promising approach. In this work, we propose a facile "hot-node" growth strategy for the preparation of millimeter-sized high luminescence 3D RE micro-networks (RE-MNs) using citric acid (CA) as a ligand with weak absorption and mismatched energy levels of RE 3+ ions. A unique assembly mechanism for RE-MNs is revealed, mainly including RE 3+ /CA coordination, high temperature-promoted disordered aggregation, "hot-node" formation, and the "hot-node" controlled production of MNs. Surprisingly, the luminescence efficiency of RE-MN assemblies is ∼10 2 times stronger than that of RE 3+ /CA complex precursors. Based on detailed photoluminescence (PL) spectra analysis, the significantly enhanced PL is directly attributed to the symmetry deviation induced transition (SDIT) effect. The formation of RE-MN assemblies results in the decrease of symmetry of the coordination environment of RE 3+ ions and leads to the deviation of RE 3+ from the center of inversion, which directly changes the originally Laporte-forbidden f–f transition to an allowed transition. Such facile and gram-scale synthesis technology enables the formation of high luminescence RE-MN assemblies with narrow bandwidth emission with promise for application in light emitting diodes (LEDs).